Distinctive ligand‐binding specificities of tandem PA14 biomass‐sensory elements from Clostridium thermocellum and Clostridium clariflavum. Issue 11 (25th June 2019) - Grinberg, Inna Rozman; Yaniv, Oren; de Ora, Lizett Ortiz; Muñoz‐Gutiérrez, Iván; Hershko, Almog; Livnah, Oded; Bayer, Edward A.; Borovok, Ilya; Frolow, Felix; Lamed, Raphael; Voronov‐Goldman, Milana
Abstract: Cellulolytic clostridia use a highly efficient cellulosome system to degrade polysaccharides. To regulate genes encoding enzymes of the multi‐enzyme cellulosome complex, certain clostridia contain alternative sigma I (σ I ) factors that have cognate membrane‐associated anti‐σ I factors (RsgIs) which act as polysaccharide sensors. In this work, we analyzed the structure‐function relationship of the extracellular sensory elements of Clostridium ( Ruminiclostridium) thermocellum and Clostridium clariflavum (RsgI3 and RsgI4, respectively). These elements were selected for comparison, as each comprised two tandem PA14‐superfamily motifs. The X‐ray structures of the PA14 modular dyads from the two bacterial species were determined, both of which showed a high degree of structural and sequence similarity, although their binding preferences differed. Bioinformatic approaches indicated that the DNA sequence of promoter of sigI / rsgI operons represents a strong signature, which helps to differentiate binding specificity of the structurally similar modules. The σ I4 ‐dependent C. clariflavum promoter sequence correlates with binding of RsgI4_PA14 to xylan and was identified in genes encoding xylanases, whereas the σ I3 ‐dependent C. thermocellum promoter sequence correlates with RsgI3_PA14 binding to pectin and regulates pectin degradation‐related genes. Structural similarity between clostridial PA14 dyads to PA14‐containing proteins in yeast helped identify another crucial signature element: the calcium‐binding loop 2 (CBL2), which governs binding specificity. Variations in the five amino acids that constitute this loop distinguish the pectin vs xylan specificities. We propose that the first module (PA14 A ) is dominant in directing the binding to the ligand in both bacteria. The two X‐ray structures of the different PA14 dyads represent the first reported structures of tandem PA14 modules.